10.4k views
4 votes
Solve: 2 ln 3 = ln(x - 4)​

User Akash Deep
by
6.0k points

2 Answers

3 votes

2 ln 3 = ln(x-4)

ln(3^2) = ln(x-4)

3^2 = x - 4

x = 3^2 +4 = 9 +4 = 13

User Ryan Kempt
by
6.0k points
1 vote

Answer:

The value of x is:


x=13

Explanation:

We are asked to solve the equation:


2\ln 3=\ln (x-4)

i.e. we are asked to find the value of x which satisfies the equation.

We know that:


a\ln b=\ln b^a

i.e.


2\ln 3=\ln 3^2\\\\i.e.\\\\2\ln 3=\ln 9

i.e. the equation is written as:


\ln 9=\ln (x-4)

Now on taking exponential on both the side of the equation we get:


e^(\ln 9)=e^(\ln (x-4))\\\\i.e.\\\\9=x-4

since,


e^(\ln x)=x

Hence, we get:


x=9+4\\\\i.e.\\\\x=13

The answer is:
x=13

User NieAR
by
6.5k points